Implementasi Pembelajaran Deep Learning Berbasis Problem Based Learning dalam Mata Pelajaran Fiqih di MAS Al-Mashuriyah Pagelaran Cianjur - Toha, Muhammad; Neng Nurpah Saparisma; Zahra Nurma Triyani; Ai Napisah; Muhammad Hakeki (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This study examines the implementation of deep learning integrated with Problem Based Learning (PBL) in Fiqh subjects at MAS Al-Mashuriyah Pagelaran Cianjur. Using a descriptive qualitative design, data were gathered through classroom observations, interviews with teachers and students, and documentation across six instructional meetings in grades XI and XII. The results show that the combination of deep learning and PBL substantially increases students’ active participation and encourages them to think more critically, especially when studying purification (thaharah) materials. Through group discussions, case-based problems, and guided exploration of Islamic legal sources, students were able to connect theoretical concepts to everyday religious practices. This approach allowed learning to shift from memorization toward deeper conceptual understanding and contextual application. The teacher served primarily as a facilitator, providing direction and scaffolding while giving students space to analyze, argue, and draw conclusions independently. Overall, the findings indicate that integrating deep learning with PBL is an effective pedagogical strategy for enhancing the quality of Fiqh learning at the madrasah level, as it not only improves comprehension but also fosters analytical thinking, collaboration, and the ability to apply Islamic legal principles in practical situations.